2018
DOI: 10.14202/vetworld.2018.1385-1396
|View full text |Cite
|
Sign up to set email alerts
|

Demographic aspects of human hydatidosis in Iranian general population based on serology: A systematic review and meta-analysis

Abstract: Aim:Human cystic echinococcosis (CE), caused by the larval stage of Echinococcus granulosus cestodes, is a globally distributed chronic disease that is an important socioeconomic and public health problem in humans and livestock in developing countries, including Iran. The aim of this study was to determine the overall seroprevalence of hydatid infection in the general population of Iran.Materials and Methods:This systematic review began by searching electronic databases in English (PubMed, Science Direct, Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Gholami in 2018 conducted a meta analyse beetwen 1995-2015 among 40 different study (totally 3090 cases). Results showed that spread of the disease in rural regions is more abundant than in urban areas (18). But in the other study in northern of Iran between 2005-2015 showed that the infection rates in urban population were higher than the rural people (19).…”
Section: Incidence Of Cystic Echinococcosis In the East Azerbaijan Iranmentioning
confidence: 87%
“…Gholami in 2018 conducted a meta analyse beetwen 1995-2015 among 40 different study (totally 3090 cases). Results showed that spread of the disease in rural regions is more abundant than in urban areas (18). But in the other study in northern of Iran between 2005-2015 showed that the infection rates in urban population were higher than the rural people (19).…”
Section: Incidence Of Cystic Echinococcosis In the East Azerbaijan Iranmentioning
confidence: 87%
“…The larval stage of the cestode parasite Echinococcus granulosus sensu lato ( E. granulosus s. l.) causes cystic echinococcosis (CE) also known as cystic hydatid disease, a chronic parasitic zoonosis of humans and domestic and wild mammals. CE is a disease of poverty and usually occurs in herding communities [ 1 , 2 ]. Canids are the definitive hosts of E. granulosus and herbivores (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Other affected organs include the spleen, heart, brain, kidney, peritoneum and bone [ 6 ]. The clinical manifestations of CE are broad, ranging from clinically silent cysts [ 7 ] to anaphylactic shock caused by the rupture of cysts and spillage of their contents [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Serological methods for the diagnosis of HCL have a high Se (38% -93%) and Sp (80% -100%). A meta-analysis conducted by Iranian researchers of the incidence of echinococcosis, based on seropositivity, showed that 6.0% of the total population is infected and the above method is specific for HCL, with Sp 95.1% (8). Previous authors have also identified US as the most sensitive method for diagnosing HCL of types CE3 -CE5, with Se 97.6% and Sp 99%; these authors also emphasize that US is sensitive and specific for determining HCL types CL and CE1 -CE3 in children (6).…”
Section: Discussionmentioning
confidence: 99%